Soil Physics: Agricultural and Environmental Applications - H.Don Scott; H.Don Scott (New Delhi Wiley, 2000)
This book describes the physical properties affect agriculture and the environment.
Environmental Applications Soil Texture Soil Temperature
Keywords: Environmental Applications; Soil Texture; Soil Temperature